The historiosophy of Stanisław Ignacy Witkiewicz - Mołdysz, Robert (Folia Philosophica, 2007)
The author of the article reconstructs the historiosophy of Witkacy, and makes an attempt to verify its main theses. A historical-philosophical reflection shown in The New Forms of Painting and Unwashed Souls concerns a disappearance of “metaphysical feeling” accompanied by the fall of “spiritual culture” (religion, philosophy, art) and development of “socialisation” supportive to a collective culture (science, common good, justice). A vision of the history of Witkacy is, according to the author, deterministic in character. Also, it is pointed out that the fall of “high culture”, foreseen by the philosopher as early as at the beginning of the 20th century, has not occurred out of the thin air, and the basic theses of his historiosophy can be positively verified.